2018
DOI: 10.4049/jimmunol.1601942
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5-Regulated Macrophage Polarization Supports the Proinflammatory Function of Macrophages and T Lymphocytes

Abstract: Macrophages are exquisite sensors of tissue homeostasis that can rapidly switch between pro- and anti-inflammatory or regulatory modes to respond to perturbations in their microenvironment. This functional plasticity involves a precise orchestration of gene expression patterns whose transcriptional regulators have not been fully characterized. We had previously identified the transcription factor NFAT5 as an activator of TLR-induced responses, and in this study we explore its contribution to macrophage functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…16a-e, the lentivirus (NFAT5-siRNA-LV) could silence NFAT5 expression in M-MDSCs and macrophages, but did not affect NFAT5 in PMN-MDSCs and CD3 + T cells at either the mRNA or protein level. In the tumourbearing mice treated with HSD, NFAT5 silencing in M-MDSCs and macrophages (though adoptively transferred NFAT5deficient macrophages in vivo could weaken antitumour capacity 26 ) could partly restore tumour growth, because PMN-MDSC's function switch affected by HSD could also display Fig. 4 HSD promoted MDSC differentiation and functional transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16a-e, the lentivirus (NFAT5-siRNA-LV) could silence NFAT5 expression in M-MDSCs and macrophages, but did not affect NFAT5 in PMN-MDSCs and CD3 + T cells at either the mRNA or protein level. In the tumourbearing mice treated with HSD, NFAT5 silencing in M-MDSCs and macrophages (though adoptively transferred NFAT5deficient macrophages in vivo could weaken antitumour capacity 26 ) could partly restore tumour growth, because PMN-MDSC's function switch affected by HSD could also display Fig. 4 HSD promoted MDSC differentiation and functional transformation.…”
Section: Resultsmentioning
confidence: 99%
“…As a typical environmental stress sensed by cells, hypertonicity induced by highsalt intake can trigger immune responses in macrophages mediated by transcription factors, such as the tonicity-responsive enhancer-binding protein (NFAT5) 25 . Studies have demonstrated that the p38/NFAT5 axis enhances the expression of a number of pro-inflammatory genes and the survival of macrophages 26,27 . However, whether high-salt intake similarly influences the functions of MDSCs in the body is unknown.…”
mentioning
confidence: 99%
“…Previous work has shown that NFAT5 induces diverse pro-inflammatory genes in response to TLRs and classical macrophage polarization (Buxadé et al, 2012; Tellechea et al, 2018). Gene set enrichment analysis (GSEA) of a previously published NFAT5-regulated transcriptome in macrophages stimulated with the TLR4 ligand LPS (Buxadé et al, 2012) identified enhanced expression of ISGs in NFAT5-deficient macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NFAT5 occupies a distinct functional niche in the control of antipathogen responses by attenuating IFN-I gene induction while enhancing expression of other inflammatory mediators (Buxadé et al, 2012; Tellechea et al, 2018). This unique duality is the result of the mechanism through which NFAT5 inhibits IFN-I expression by opposing IRF3, the master transcription factor specialized in IFN-I expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation